PERCEPTION OF TARGET HOUSEHOLD MEMBERS ON HOPE FAMILY PROGRAM IN DRADAHBLUMBANG KEDUNGPRING LAMONGAN - Nashihin Nashihin; Iwan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2019)
Factually, the household poverty rate tied to health and education. Low and weak household income below the poverty line causes such households are unable to meet the needs of especially the health and education needs. This study aimed to describe and analyze the perceptions of members of the target households in the village hope the family program in Dradahblumbang Kedungpring Lamongan and to describe and analyze the factors that affect the internal and external perception of members of targeted household member against family program expectations in Dradahblumbang Kedungpring Lamongan. Data were analyzed by three steps, ie condensation of data, a data display, and conclusion drawing or verification. The analysis shows that Member targeted households desperately need their family program this expectation, they are well aware that with this program hope their families will receive cash assistance to alleviate the needs of family life, particularly for school fees and for other purposes. Targeted household members' opinions on the implementation of validation and updating data is generally